RELIABILITY OF 18a (H) OLEANANE BIOMARKER AS AGE INDICATOR OF SOURCE DEPOSITION - MAHMOODI, SYED MUHAMMAD IBAD (2014)
This study aims to evaluate the reliability of 18a(H)-01eanane biomarker as an age indicator of source deposition. The problem arises when a tertiary reservoir oil contains tertiary biomarker 18a(H)-01eanane to justify the source of oil. Reliability of oil-source correlation using biomarker is dependable only when the specific biomarker is not age equivalent of the reservoir. Oil in Tertiary reservoirs cannot be confirmed by Tertiary biomarkers as generated from Tertiary source because of the possibility of contamination. 18a(H)-01eanane as an age indicator of source deposition has been tested here and the results show this specific biomarker can be introduced in the oil as contamination if the reservoir holds 18a(H)-01eanane biomarker in pore waters in the pre-migration condition. Thus it is concluded that although Oleanane is restricted within Late Cretaceous to Tertiary periods, the presence of this biomarker in oils of Late Cretaceous to Tertiary reservoirs cannot justify the age of the source of oil. This inference may be universally true for all the biomarkers that need to be confirmed by using other biomarkers.